O riso da musa no campo de batalha: as marcas da poesia de Arquíloco na formação da persona poética na comédia ática - Amaro, Márcio Henrique Vieira (2020)
The poetry of Archilochus of Paros was widely spread in the ancient world. In Brazil, however, the most relevant works on its production are still few and recent. We know that the iambographic tradition in which the poet is inserted represents an important link in the genesis of the dramatic comic genre, which reverberated strongly in the work of early comediographers such as Cratino, Emolis and Aristophanes. The study of ancient comedy has long been restricted to Aristophanes' superstitious texts, but since the publication of the work The Rivals of Aristophanes (1996), a process of revitalizing the study of his contemporaries has begun. The superstitious comedies of Aristophanes cannot, despite their color and the diversity of everyday scenes in Athens described in them, be read outside the poetry that precedes or dialogues with it; and, therefore, it is necessary to insert it both in the iambographic chain of which she is a daughter and in the group of her rivals. Thus, we believe that the archilochean poetic persona and its presence in the comedy of Cratino and Aristophanes are extremely valid. We chose to make this dialogue between ancient genres starting from Archilochus of Paros, as representative of the iambographic tradition, as well as Cratino, one of the first comedians of the first generation and ending with Aristophanes, his great rival and representative of the transition between old comedy and comedy. average. We will check the process of construction of the poetic archiloquian persona to see what affects and reverberates in the comic genre. The analytical instruments of the research will be both of philological and intertextual criticism. As a theoretical reference we will use Harvey and Wilkins's collection, The Rival of Aristophanes: Studies in Athenian Old Comedy (1996), from Paula da Cunha Correa's research, contained in the book Armas and Varões: War in the Lyric of Archilochus (1998), and from Rostein's works, The Idea of Iambos (2010), Cratinus and the Art of Comedy (2010), by Emanuela Bakola and Zachary Biles' Aristophanes and the Poetics Competition (2011).